Political Turmoil in ECOWAS: When Politics Prevails Over Law - Adu Yao Nikez; Mezyaev Alexander Borisovich (Ученые записки Института Африки Российской академии наук)
Several military regimes have recently come to power within the Economic Community of West African States (ECOWAS). This article on the political crisis in ECOWAS examines the main causes of these developments in the region and the approaches of regional organizations to address them in the African context, taking into account the practices of the OAU and the African Union. In the first phase, ECOWAS imposed a series of sanctions against these states for violating their international legal obligations in the areas of democracy, human rights, the rule of law, and good governance. In addition, the community decided to use military force in the Republic of Niger in order to free M. Bazoum, and, in response to this threat, Mali, Burkina Faso, and Niger decided, on September 16, 2023, to create the Alliance of Sahel States (ASS) for self-defense to repel the aggression of the ECOWAS troops.